PERTUMBUHAN EKONOMI, KETIMPANGAN PENDAPATAN DAN TINGKAT PARTISIPASI ANGKATAN KERJA ATAS PENETAPAN UMK KEWILAYAHAN - Rahmat Alhakim (INUMIYA: Jurnal Ekonomi Pembangunan, 2022)
Determination of District Minimum Wage in Cilacap Regency is different from 35 regencies / cities in Central Java which aims to stimulate investment from private parties and even distribution of development in all regions in Cilacap Regency, the basis of this research. The variables used are determination of Regency Minimum Wage, Population Growth and Industrial Sector Contribution to GRDP, Inequality of Inter-Area Income and Labor Force Participation Rate in Cilacap Regency Central Java Province 2008-2015. The data used is secondary data from the Central Bureau of Statistics (BPS) Cilacap Regency analyzed using panel data regression. The results showed that: Determination of District Minimum Wage, Population Growth and Industrial Growth have positive and significant impact to Gross Regional Domestic Product (GRDP). Regency Minimum Wage has an non-significant effect on income inequality between regions, while population growth and industrial sector growth have a significant effect on income inequality among regions, for variable of population growth have positive effect, while industry sector have negative effect. Regency Minimum Wage has positive (non-significant) influence on labor force participation rate, while population growth and industrial sector growth have significant effect to income inequality among region, for variable of population growth have negative effect while industry sector have positive effect.